Penatalaksanaan COVID-19 Pada Penderita Penyakit Ginjal - Siti Cholishotul H; Abdur Rohman (PROCEEDING UMSURABAYA, 2023)
AbstractCovid-19 is acute respiratory syndrome due to Coronavirus SARCoV-2 infection. Virus attaches to angiotensin converting enzyme 2 (ACE2) receptor, besides the lungs, this receptor also expressed by cells in kidney causes renal insufficiency. Covid-19 patients with chronic kidney disease (CKD) management is the same as other Covid-19 patients, antivirals, renal function replacement therapy, and supportive therapies. ERA-EDTA Europe, reported 5596 cases of Covid-19 and 1331 deaths among hemodialysis patients in 2020. Concerns about the vulnerability of CKD patients group are increasing amid the pandemic. Standard operating procedures have proven effective in preventing the spread of Covid-19 among CKD patients undergoing hemodialysis.Keywords : COVID-19, chronic kidney disease (CKD), therapy, preventive